Audit of the Transition of Manual to Digital Service Systems at Spacebox Self Photo Studio Medan Using Framework Pieces - Yanty Faradillah; Dafa Syahreza; Inaya Nur Wahidah; Adli Fadlurrahman Aziz; M Farhan Ghany; Kissi Lola Armedia Br. Siregar; Syahla Agrivina Azzuhrah; Syafira Wahyuni; Nabila Meisya Lubis; Selvi Amalia (Cattleya Darmaya Fortuna, 2026)
The acceleration of the creative industry in the independent photo studio sector in Medan City demands modernization of operational management to maintain business performance. This study audits the digitalization of services at Spacebox Self Photo Studio Medan, which migrated from a paper-based recording system to a QR Code-based self-queue platform (on-site self-registration). This transformation was triggered by operational constraints such as physical queue buildup, high multitasking workloads for cashier operators, and vulnerability to financial data manipulation. Using a descriptive qualitative methodology, the effectiveness of this technology transition was comprehensively evaluated through the PIECES Framework (Performance, Information, Economics, Control, Efficiency, Service) and the Balanced Scorecard instrument. Primary data was collected through field observations, in-depth interviews with operational staff, and monitoring satisfaction metrics on a customer feedback dashboard. The audit results confirmed that the implementation of this integrated digital system successfully reduced administrative waiting times, cut logistics costs through a paperless concept, minimized human error in the visualization of daily and annual turnover, and optimized operator work productivity. Overall, this transition succeeded in creating studio governance that is transparent, structured, and responsive to customer needs.